ANALISIS PENGARUH BIAYA AGENSI, TAHAP DAUR HIDUP PERUSAHAAN DAN REGULASI TERHADAP KEBIJAKAN DEVIDEN Studi Kasus Pada Jakarta Islamic Index (JII) - Sutrisno Sutrisno (Universitas Islam Negeri Alauddin Makassar, 2017)
The purpose of this study is to investigate the influence of agency costs, life cycle, and regulation of the devidend policy. The populations in this study were 72 companies that enter into the Jakarta Islamic Index (JII) listed on the Indonesia Stock Exchange period 2011-2014. The sample is selected by purposive sampling method, ie sampling technique using a certain consideration which is relevant to the selected sample research purposes. The number of samples obtained were 23 companies listed on the Indonesia Stock Exchange. Data analysis were performed by classic assumption test and multiple regression analysis. The results of this study indicate that free cash flow, dispertion of ownership, and life cycle do not take effect the devidend payout ratio. The institutional of ownership is significantly negative and take effect on devidend payout ratio. Regulation influenced positively and significantly to devidend payout ratio.